Determining the Prevalence of Attention Deficit Hyperactivity Disorder (ADHD) in Patients with Bipolar Disorder Type I (BID) within Their Remission Phase: - Bidaki, Reza; Ghaffary, Azadeh; Hosseinpoor, Sara (Galen Medical Journal, 2013)
Background: There have been several studies conducted on the relationship between bipolar mood disorder and attention deficit hyperactivity disorder (ADHD) during the recent years, and in most of them the rate of this association had been estimated as 22-90% and had been reported as noticeable. The goal of this study is to determine the prevalence of ADHD in patients with Bipolar mood disorder type I (BID). Materials and Methods: In this Cross-sectional study, 152 patients with BID that were referred to psychiatric clinic of Tehran psychiatric Institute for a better observation and treatment were included. Two questionnaires, Wender’s for childhood ADHD and Conner’s’ for adulthood ADHD were filled by the patients. Results: 102 patients (67%) were males and 50 were females. The average age of patients at the time of our study (with the minimum of 17 and maximum of 76) was 33.5±10.9. The prevalence of ADHD in our patients was 11.8%. 46 people (30.9%) had a history of childhood ADHD. 21 persons had adult ADHD from whom only 3 ones mentioned a history of childhood ADHD (which means 18 people of our adulthood ADHD had no history of childhood ADHD). Conclusion: Since some treatments lead to improvement of ADHD and worsening of BID, investigations on their correlations and their alternative treatments seemed to be necessary. This study showed a significant correlation between ADHD and BID, which was similar to the results of other studies in this field.